2015
DOI: 10.1128/jcm.00899-15
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens-Related Infectious Keratitis with White Plaque Formation Caused by Corynebacterium propinquum

Abstract: We report the first case of Corynebacterium propinquum keratitis in the compromised cornea of a diabetic patient wearing therapeutic contact lenses. The strain was identified to the species level based on sequencing of the 16S rRNA gene and RNA polymerase ␤-subunit-encoding gene (rpoB). Ophthalmologists should be aware of nondiphtherial corynebacterial infection of compromised corneas. CASE REPORT This case consisted of a 44-year-old woman with a history of type 1 diabetes, hemodialysis due to diabetic nephrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…However, in immunocompromised patients, many recent reports have demonstrated that Corynebacterium species can be potentially pathogenic when present on the ocular surface [ 7 , 8 , 9 , 10 ], as this infection has been associated with cases of endocarditis of the aortic and mitral valves [ 11 ], granulomatous mastitis [ 12 ], and pelvic osteomyelitis [ 13 ]. Many reports have been based on the case series [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Therefore, the frequency of occurrence of various Corynebacterium species on the ocular surface compared to other organs is not well characterized, and the mechanism by which Corynebacterium species function as pathogenic organisms is also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, in immunocompromised patients, many recent reports have demonstrated that Corynebacterium species can be potentially pathogenic when present on the ocular surface [ 7 , 8 , 9 , 10 ], as this infection has been associated with cases of endocarditis of the aortic and mitral valves [ 11 ], granulomatous mastitis [ 12 ], and pelvic osteomyelitis [ 13 ]. Many reports have been based on the case series [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Therefore, the frequency of occurrence of various Corynebacterium species on the ocular surface compared to other organs is not well characterized, and the mechanism by which Corynebacterium species function as pathogenic organisms is also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (MR-CNS) are highly resistant to various antibiotics [ 2 , 4 7 ]. It has recently been reported that Corynebacterium can cause ocular surface infection, even though it is considered to be a non-pathogenic organism [ 8 12 ], and fluoroquinolone-resistant Corynebacterium has become a growing issue of concern [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include skin abscesses, endocarditis, bacteremia, and infections of the lower respiratory system. 7 Several conjunctival 3,8 and corneal 3,9 isolates are mentioned in the microbiological literature. The clinical details were given for 1 corneal infection involving a diabetic woman who wore bandage contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical details were given for 1 corneal infection involving a diabetic woman who wore bandage contact lenses. 9 The isolate was identified as C. pseudodiphtheriticum in biochemical testing but as C. propinquum in rpoB gene sequencing. The patient was treated with intravenous ampicillin and topical gatifloxacin and cefmenoxime.…”
Section: Discussionmentioning
confidence: 99%